The moderator role of Customer Characteristics in the relationship between E-marketing and Mental Image Sudanese Bank Customers in 2022 - Elsheikh Eltahir, Sana GadAlla; Idris, Abdullah Muhammad Ali; Ahmed, Sultan Muhammad; Mahmoud, Muhammad Ahmed (Journal of Economic, Administrative and Legal Sciences, 2023)
The purpose of this study is to investigate the moderator role of Customer Characteristics in the relationship between Electronic marketing and Mental Image. The study method was descriptive. the study adopted on improbability sample, where (250) questionnaire were distributed a response rate of (100%), the questionnaire has been designed and distributed on a total number of questionnaires. the validity of the questionnaire was confirmed by reliability data the study used factor analysis, Used (SPSS) and (AMOS) Cranach alpha and Structural Equation Modeling. The study has developed the hypotheses and measured, the findings revealed there is not effect between Electronic market and Mental Image, and there is not directed impact of Website on the cognitive dimension, and there is not directed impact of the Website on the social dimension, and there is not directed impact of Electronic mail on the cognitive dimension, and there is not directed impact of the Electronic mail on the social dimension, Customer Characteristics (sex, age, education) there is not modify the relationship between Electronic market and Mental Image. Depend on the results of the study have been discussed results, also have been made recommendations and suggestions for future researches. The study recommended for intensifying the social responsibility activities; as well as working for meeting both customers need and community to achieve the competitive advantage.